Ez-Crutches 2.0: an innovation of assistive device for disabled person / Suzana Yusof ... [et al.] - Yusof, Suzana; Sharif Abdullah, Sharifah Shafinaz; Sham, Fatimah; Shohor, Norhafizatul Akma (2021)
Successful management of disabled person including those with medical conditions especially at lower limbs (legs) is a critical and long term process that can be compromised by many factors such as late ambulation and rehabilitation. Though the usage of assistive devices is established for any types of limbs-related condition, such as a wheelchair, walking frame and elbow crutches; the use of axillary crutches is the most common and convenient one. These axillary crutches are assistive devices that help the disabled person in the process of early ambulation, which can provide support to the weak, injured, fractured or post-operated leg. Thus, this project aims to innovate the axillary crutches into the most client-friendly to support the disabled person in the recovery process, which is named Ez-Crutches 2.0. This innovation provides an enhancement in handling axillary crutches without hustle. Imagine if the disabled persons are using the common axillary crutches, when they want to reach something above the head, they need to uplift hands and leave the crutches to fall down. It is difficult for them to pick up the laid crutches from the floor, and it may lead them to fall and cause further injuries. In clinical settings, early ambulation process supported with assistive devices would contribute to faster recovery process, improve the person's quality of life, have a sense of independence, and improve management outcomes. Therefore, the Ez-Crutches 2.0 will offer a new potential device that contributes in the enhancement of therapeutic intervention in the medical field especially for those disabled persons.